The Effect Of Working Capital Turnover, Profitability, Liquidity And Solvency On Stock Prices: Study of the Telecommunications Sub Sector Listed on the Indonesian Stock Exchange for the 2013 – 2022 Period - Yudha, Muhammad Bentar Brahmin; Muktiadji, Nusa; Nurisnaini, Neni (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine the effect of working capital turnover, profitability, liquidity, solvency on the stock price of telecommunication companies for the period 2013 - 2022, both partially and simultaneously. The financial ratios studied are: Working Capital Turnover (WCTO), Net Profit Margin (NPM) Current Ratio (CR) and Debt Equity Ratio (TATO) to stock prices. The population in this study is the telecommunications subsector listed on the Indonesia Stock Exchange (IDX) from 2013 to 2022. The research sample was 7 telecommunications sector companies obtained using purposive sampling technique. The data collection technique used is documentation. Data analysis was carried out using panel data analysis techniques. The results shown that partially the Working Capital Turnover, Profitability, and Solvency variables had a significant positive effect on stock prices. While the Liquidity variable has no significant effect on stock prices. However, the results of the study simultaneously variables Working Capital Turnover, Profitability, Liquidity, Solvency affect stock prices. Keywords: Working Capital Turnover, Profitability, Liquidity, Solvency on Stock Price